Causes and Effects of Damage Materials to the Printing Business in Barangay Tandang Sora, Quezon City : Vol.3, No.1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Most printing businesses face failure and significant challenges in acquiring new technologically advanced printing machines and equipment. Shortage of skilled workers and improper handling of printing materials in production are the most common problems encountered and observed inside the printing business. This shortcoming contributed to increased damages and defects in the materials in the workplace. This study aims to determine the causes of damaged materials during the production process and its effects on the business. It also aimed to solve those causes and minimize the effects by crafting a guideline to improve the quality of work in printing. This study utilised a qualitative research method design and random sampling technique. The researchers used survey questionnaires, actual observations, interviews, and statistical data analysis as the primary instruments to gather informative data that can benefit the present research topic. This study also used the following statistical tools: percentage frequency and weighted mean to analyse the data gathered in a suitable form for the appropriate results and conclusions. Based on the results gathered in the survey questionnaire on the demographic profile of the respondents when it comes to their age, gender, educational attainment, and working hours. Most employees working in the printing business are between 18 and 29 years old, and most are male. As for their educational attainment, 31 responded that they are at the college level, and the remaining employees are at the SHS/High School level. As for the working hours, most of them are working up to 5-10 hours in printing. The researchers proposed the following guidelines for preventing waste in the printing business: it includes guidelines on the management, employees, and company policies for the customers. The guidelines would benefit the printing businesses in maintaining quality work.
Keywords: causes; effects; damages materials